A Nonuniform Modulated Complex Lapped Transform - Malvar, Henrique S.; Xiong, Zixiang (2000)
A nonuniform modulated complex lapped transform (NMCLT) is introduced in this paper as a two-stage extension of the modulated complex-lapped transform (MCLT). The NMCLT is a new nonuniform oversampled filter bank with a better combination of time and frequency-domain localization than previous designs. Adaptive nonuniform subband decompositions can be easily generated by varying the number of coefficients brought to the second stage on a frame-by-frame basis. The NMCLT is ideally suited for processing wideband signals such as audio, with reduced time-spreading artifacts.